PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR, QUALITY OF WORK LIFE, DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PUSKESMAS KECAMATAN PAGAK - Nadia Ike Febiyanti; Kristina Sedyastuti; Puspitosari Suharso, Arien Anjar (ITB AAS Indonesia Surakarta, 2025)
This study aims to examine the impact of OCB, QWL, and job satisfaction on the performance of employees at Puskesmas Kecamatan Pagak. Utilizing quantitative primary data, the entire employee population was included in this research. A saturated sample comprising 58 employees was selected. Data collection was conducted through questionnaires employing a Likert scale, and the analysis utilized multiple linear regression via SPSS 22. Findings indicate that these three variables significantly and simultaneously influence employee performance. Additionally, OCB, QWL, and job satisfaction each contribute significantly and partially to employee performance. This suggests that enhancing these three elements can lead to improved performance among employees at Puskesmas Kecamatan Pagak. Future research is encouraged to investigate additional variables outside the scope of this study that may also impact employee performance. Keywords : organizational citizenship behavior, quality of work life, job satisfaction, performance employees